A new living lab for usability evaluation of ICT and next generation networks for elderly@home - Teixeira, A.; Rocha, N.; Dias, M. S.; Braga, D.; Queirós, A.; Pacheco, O.; Fonseca, J. A.; Pinto, J. S.; Gamboa, H.; Corte-Real, L.; Fonseca, J.; Martins, J. A.; et al. (Proceedings of the 1st International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications - AAL, (BIOSTEC 2011), 2011)
Living Usability Lab for Next Generation Networks (www.livinglab.pt) is a Portuguese industry-academia collaborative R&D project, active in the field of live usability testing, focusing on the development of technologies and services to support healthy, productive and active citizens. The project adopts the principles of universal design and natural user interfaces (speech, gesture) making use of the benefits of next generation networks and distributed computing. Therefore, it will have impact on the general population, including the elderly and citizens with permanent or situational special needs. This paper presents project motivations, conceptual model, architecture and work in progress.